2010
DOI: 10.1097/coc.0b013e3181b9cedc
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Polymorphisms of ERCC1 and XPD and Clinical Response to Platinum-Based Chemotherapy in Advanced Non–Small Cell Lung Cancer

Abstract: The polymorphic status of ERCC1 might be the promising ancillary marker for predicting treatment response of advanced stage NSCLC patients. The DNA microarray-based method is accurate, high-throughput and inexpensive, suitable for SNP genotyping in a large number of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
3
37
0
2
Order By: Relevance
“…Previous studies have demonstrated the correlation between gene polymorphisms involved in DNA repair and chemotherapy response (33,34). By means of testing peripheral blood, our team has already done some work in assessing the role of DNA repair gene polymorphisms including XPA and XPD in the response of platinum-based regimen in advanced NSCLC patients (12,20,21,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the correlation between gene polymorphisms involved in DNA repair and chemotherapy response (33,34). By means of testing peripheral blood, our team has already done some work in assessing the role of DNA repair gene polymorphisms including XPA and XPD in the response of platinum-based regimen in advanced NSCLC patients (12,20,21,35).…”
Section: Discussionmentioning
confidence: 99%
“…The genotyping procedure involved polymerase chain reaction (PCR) and the three-dimensional (3-D) polyacrylamide gel-based DNA microarray method (23). Probes and primers were designed by Primer Premier 5.0 software as previously described (20,21). One of each pair primers was modified with acrylamide phosphoramidite (Acrydite TM ; Matrix Technologies, Hudson, USA) at 5′-terminal.…”
Section: Dna Collection and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had reported that patients carrying the ERCC1 CC genotype or C allele at C118T had a higher response rate to platinum-based chemotherapy Kalikaki et al, 2009;Li et al, 2010). Isla et al (2004) and Ryu et al (2004) both found that advanced NSCLC patients with the ERCC1 118 CC genotype had better survival, but no relationships were found between the response and 118 CC genotype after platinum-based treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Preclinical data suggests that the ERCC1 C8092A and C118T polymorphisms could affect the ERCC1 mRNA and protein levels, thus leading to different platinum sensitivity and increased DNA repair capacity (Chen et al, 2000;Yu et al, 2000;Park et al, 2002). ERCC1 polymorphisms have been reported to predict better response Kalikaki et al, 2009;Li et al, 2010) or survival in NSCLC patients treated with platinum-based chemotherapy Ryu et al, 2004;Zhou et al, 2004). However, published reports of the associations between ERCC1 SNPs and clinical efficacy from individual studies are controversial (de las Peñas et al, 2006;Tibaldi et al, 2008;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%